Implementasi Program UKM English Club Mahasiswa Non-English Department - Noviyanti, Masyitah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This research aims to find out how was the implementation of The English Club program, especially for non-English department students in Nahdlatul Ulama Sidoarjo University (UNUSIDA), as well as to know about the obstacles during the implementation. This research is a qualitative descriptive research, to collect the data, this research used interviews, observations and documentation. The data analysis technique used is qualitative data analysis, namely data collection, data reduction and conclusion. The results showed that English Club, has four main activities, namely English Conversation, English Course, English Fest and Creative Writing. The success of the implementation program can be seen through four aspects such as; kind of programs, material, Tutor quality, and learning environment. The data research showed that 75% respondents strongly agree that the implementation of English club programs has succeed. There are some obstacles of the implementation of English club programs such as; Sidoarjo is the red zone of Covid-19 pandemic, so several program cannot run well. It is difficult to arrange the schedule which should be suitable for all the members from different program study. The last is the busyness of English Club members with other activities outside the English Club.